Visualization of the Distribution of Formal and Non-Formal School Locations in Asahan Regency Based on GIS - Sarmila Sarmila; Novica Irawati; Afdhal Syafnur (Ali Institute of Reseach and Publication, 2025)
Equal access to education remains a key challenge in the development of human resources at the regional level. Asahan Regency is home to a variety of formal and non-formal educational institutions spread across multiple districts. However, the distribution data of these institutions is still fragmented and not yet integrated into a centralized system. This study aims to map the locations of formal and non-formal schools registered under the Department of Investment and One-Stop Integrated Services (DPMPTSP) in Asahan Regency using Geographic Information System (GIS) technology. The developed system presents spatial information through an interactive digital map that helps the public locate schools according to their needs and supports the local government in planning equitable distribution of educational facilities. In addition, the system includes a feature that allows school administrators to upload administrative documents digitally, thereby streamlining the registration process at the Public Service Mall. The research employs a descriptive qualitative approach with data collection techniques such as observation, documentation, and interviews. The results show that GIS implementation effectively provides accurate visualizations of school distribution patterns and helps identify areas lacking in educational facilities. The system also enhances the efficiency of the administrative process for school licensing.